PENGARUH KUALITAS PRODUK TERHADAP KEPUASAN KONSUMEN MENGGUNAKAN PRODUK TUPPERWARE DI KOTA PALU - TRISTIYANTI, EVILIA (Fakultas Ekonomi Universitas Tadulako, 2015)
This study aims to determine and analyze the effect of product quality on customer satisfaction using Tupperware products in Palu City. The type of research used is quantitative (showing the relationship between variables). The population of this study is that the general public who have used Tupperware products are not known with certainty. Sampling technique to determine the sample that will be used in this study using the technique of non probability sampling, the purposive sampling with the number of respondents 100 people. Data collection using questionnaire. The analysis method used multiple linear regression analysis. The result of the research showed that (1) There is influence of product quality significantly to customer satisfaction by using Tupperware product in Palu City (2) There is influence of product quality with performance, suitability, endurance, aesthetics and perceived significantly to consumer satisfaction using Tupperware product in Palu City.